2015
DOI: 10.1101/014563
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictability of Autism, Schizophrenic and Obsessive Spectra Diagnosis: Toward a Damage Network Approach

Abstract: Schizophrenia, obsessive-compulsive and autistic disorders are traditionally considered as three separate psychiatric conditions each with specific symptoms and pattern of brain alterations. This view can be challenged since these three conditions have the same neurobiological origin, stemming from a common root of a unique neurodevelopmental tree. The aim of this meta-analytic study was to determine, from a neuroimaging perspective, whether i) white matter and gray matter alterations are specific for the thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 99 publications
(123 reference statements)
0
10
0
Order By: Relevance
“…GM alteration distribution is rather difficult to investigate, mainly because there is a lack of methods specifically devoted to the computation as well as the identification of a GM co - alteration pattern , that is, a type of connectivity that, instead of looking for the transmission of information, looks for the distribution of GM alterations. Recently, however, a study by Cauda et al (2015) has proposed a methodology capable of identifying the neural alterations' distribution across the brain. Authors have shown that, at least for some psychiatric disorders, it is possible to define a morphometric co - alteration network and infer a hierarchy of brain structures within the GM alterations' patterns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GM alteration distribution is rather difficult to investigate, mainly because there is a lack of methods specifically devoted to the computation as well as the identification of a GM co - alteration pattern , that is, a type of connectivity that, instead of looking for the transmission of information, looks for the distribution of GM alterations. Recently, however, a study by Cauda et al (2015) has proposed a methodology capable of identifying the neural alterations' distribution across the brain. Authors have shown that, at least for some psychiatric disorders, it is possible to define a morphometric co - alteration network and infer a hierarchy of brain structures within the GM alterations' patterns.…”
Section: Introductionmentioning
confidence: 99%
“…The present study follows the same line of research and aims at investigating the co-alteration pattern across the brain of patients with chronic pain by applying the method already developed by Cauda et al (2015) . In particular, we used a meta-analytic approach and a network-based analysis in order to address the following issues: i) do neuronal alterations occur randomly across the brain in patients with chronic pain?…”
Section: Introductionmentioning
confidence: 99%
“…Cauda et al. (2015) found that the overlapped expression profile between Ash1l and other risk genes, such as SHANK3, DISK1, and NRXN1 , is involved in chromatic regulation and neurodevelopment in early life. Mutations in Ash1l may change early brain developmental events, which is associated with neuropathological abnormalities such as migration, stratification, and proliferative defects.…”
Section: Function and Signaling Pathway Of Ash1lmentioning
confidence: 99%
“…Meta‐analysis studies identified 109 loci with pleiotropic effects, including Ash1l , associated with TS and co‐occurrence with psychiatric disorders (Brinkmeier et al., 2015; Lee et al., 2019). These conditions have the same neurobiological origin, originating from the common root of a unique neurodevelopmental tree (Cauda et al., 2015), and the shared etiology and susceptibility show considerable overlap in the common network of brain connectomes, neuroanatomically, in functional or structural aspects (Crossley et al, 2014; van den Heuvel & Sporns, 2019), indicating that an individual mutation and molecular mechanism is unlikely to underlie these diseases (Harrison & Weinberger, 2005; Toro et al., 2010). Convergent evidence shows that connectivity abnormalities, neuronal circuit problems, brain networks, and E/I imbalance are core parts of the pathology in TS, ASD, ADHD, and SCZ.…”
Section: Ash1l and Other Neurological Conditionsmentioning
confidence: 99%
See 1 more Smart Citation